Church Fathers on Ownership - Chmielarz, Małgorzata; Ilski, Kazimierz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an analysis on the concept of ownership in the selected Church Father's works. The authors focus on the work of Saint Jerome Saint Basil of Caesarea, Ambrose and Augustine, presenting the concept of ownership in the middle ages.